Environmental barriers perceived by the Finnish population with spinal cord injury: a cross-sectional survey - Saarimäki, Sanna-Mari; Reiterä, Paula; Täckman, Anni; Arokoski, Jari; Vainionpää, Aki; Kallinen, Mauri; Tallqvist, Susanna; Koskinen, Eerika; Hämäläinen, Harri; Kauppila, Anna-Maija; Anttila, Heidi; Hiekkala, Sinikka (Spinal cord, 2024)
Cross-sectional survey of the Finnish population with spinal cord injury (SCI). To explore the frequencies of perceived environmental barriers (EB) that made participation harder for the Finnish population with SCI and to compare the occurrence of perceived EBs by gender, age, time since injury, and injury severity. Participants were recruited from the registers of the three SCI outpatient clinics responsible for the lifelong care of people with SCI in Finland. The self-administered Nottwil Environmental Factors Inventory Short Form (NEFI-SF) collected in the Finnish Spinal Cord Injury Study (FinSCI) (n = 1772) was used. Nonparametric tests and multinomial logistic regression models were utilized. 880 individuals responded to the NEFI-SF items (response rate 50%). Climate was perceived as a barrier by 72% and a serious one by 44% of the respondents. The rates regarding public access were 59% and 24%, private home access 46% and 18%, and long-distance transport 45% and 20%. Four out of ten respondents reported that finances, lack of assistive devices for short-distance transport, and political decisions restricted their participation. The NEFI-SF total scores were higher (meaning more perceived restrictions by EBs) for those more severely injured. Climate, access to public and private places, challenges with transport, finances, and political decisions were the EBs most frequently perceived to restrict participation by the Finnish population with SCI. Most EBs that were prominent causes of restrictions are modifiable. Greater accessibility to the built environment, equal services to all, and positive special treatment could reduce their effects.